CHANNEL SELECTION SIMULATION WITH RAIN CONDITIONS WITH COMPARISON OF SIGNAL STRENGTH OF RECEIVER EXISTING 5G NETWORK FREQUENCY 2.3 GHZ - made sutha yadnya; Suthami Ariessaputra; Natasya Dewi Astuti (DIELEKTRIKA, 2023)
The 5G network has been used in Grand Prix 1 (GP-1) in Indonesia. In accordance with the permission granted by the Ministry of Communication and Information with a working frequency of below 900 MHZ, mid 2.3 GHz, and high 28 GHz. One of the advantages of 5G is that the download speed reaches 20 Gpbs per user using high frequencies. This study simulates by analyzing the effect of 5G network performance when there is rain attenuation which can reduce signal quality. Then a centralized RAN (C-RAN) architectural scenario is created when the BTS is dampened by rain for each of its links. Then calculating the rainfall data to become rain attenuation with ITU-R recommendations, the SNR values ​​are obtained from 3 dBm to 20 dBm, the SNR values ​​are used as input using the Maximal Ratio Combining method in order to reduce signal interference that occurs due to rain.